Matrix analysis - Horn, Roger A.; Johnson, Charles R. (Cambridge ; New York : Cambridge University Press, 2013)
"The thoroughly revised and updated second edition of this acclaimed text has several new and expanded sections and more than 1,100 exercis es"--
Machine generated contents note: 1. Eigenvalues, eigenvectors, and s imilarity; 2. Unitary similarity and unitary equivalence; 3. Canonical forms for similarity, and triangular factorizations; 4. Hermitian matri ces, symmetric matrices, and congruences; 5. Norms for vectors and matr ices; 6. Location and perturbation of eigenvalues; 7. Positive definite and semi-definite matrices; 8. Positive and nonnegative matrices; Appe ndix A. Complex numbers; Appendix B. Convex sets and functions; Appendi x C. The fundamental theorem of algebra; Appendix D. Continuous depende nce of the zeroes of a polynomial on its coefficients; Appendix E. Cont inuity, compactness, and Weierstrass's theorem; Appendix F. Canonical P airs.
Includes bibliographical references (p. 571-574) and index.
Keywords: Matrices